Patrones de uso, factores predisponentes y potenciales reacciones adversas de Flagyzol óvulo vaginal distribuido por una droguería de la ciudad de Lima - Mauricio Narciso, César André (2019)
The present report sought to determine the patterns of use, predisposing factors and potential adverse reactions of the pharmaceutical product Flagyzol (tinidazole 150 mg + miconazole nitrate 100 mg) vaginal ovule in users surveyed in the city of Lima in 2016. This as part of the plan of active pharmacovigilance that is required of holders of the sanitary registry in accordance with the guidelines of the General Directorate of Drugs, Supplies and Drugs (DIGEMID). With the continuous and probabilistic sampling method, female users older than 18 years were selected who started the use of Flagyzol vaginal ovule. They were followed up with questionnaires about the patterns of use and predisposing factors that could cause potential adverse reactions due to the use of the medication. Burning (1.28%) and vaginal bleeding (0.32%) were the potential adverse reactions, and no relationship was found for the patterns of use and predisposing factors to cause adverse reactions to the pharmaceutical product Flagyzol vaginal ovule. This study design has been an important antecedent to follow the path in the search for more information on the safety profile of Flagyzol vaginal ovule